Chemomechanical effects on the separation of interfaces occurring during fracture with emphasis on the hydrogen-iron and hydrogen-nickel system. (15th October 2015) - Kirchheim, Reiner; Somerday, Brian; Sofronis, Petros
Graphical abstract: Abstract: During fracture new surfaces are formed by a propagating crack. Depending on the chemical potential of the constituents of a material and their mobility the composition of the newly formed surfaces changes. Thus the surface energy as part of the work to fracture will be affected. This will be treated by combining the work to fracture representing the mechanical aspect and the Gibbs Adsorption Isotherm covering the chemical aspect. Compared to previous studies the present one provides a more generalized but also a simpler insight into chemomechanical effects. In extreme cases separation of lattice planes or separation of two crystals with a common interface occurs without applied external forces. Closed solutions for the work of fracture are derived for brittle fracture and surface segregation of solutes in the limit of a mean field approach. Chemomechanical effects including plastic deformation by dislocation or vacancy generation are discussed qualitatively.